PEMANFAATAN KARBON SABUT KELAPA TERIMPREGNASI UNTUK MENGURANGI TEMBAGA(II) DALAM MEDIUM AIR - Roy Andreas; Uyi Sulaeman; Tien Setyaningtyas (Universitas Jenderal Soedirman, 2008)
This research is conducted to produce carbons from coconut fibre which approach to activated carbon clause continue with carbon surface modification and the adsorption examination to Cu(II) ions. The research consist of several phase. Carbon making of coconut fibre conducted by carbonization processes at 320-400oC with temperature interval 20oC. Carbon yielded in characterized moisture content, ash content and its adsoprtion to iodium. The carbon surface modification conducted by loaded 2-mercaptobenzotiazol (MBT) on carbon. The adsorpsibility of carbon-MBT tested by influence of contact time, pH, and the isoterm adsorption pattern. The result of the study showed carbonization of coconut fibre which approach the requirement of SII No.0258-89 gained at temperature 320oC. In the present study equilibrium time of 10 minute and pH was found to be optimum for both adsorbent. While type of isothermal adsorption from carban and carbon-MBT adsorbent followed the Langmuir adsorption pattern.